Hippocampal developmental vulnerability to methylmercury extends into prepubescence - Obiorah, Maryann; McCandlish, Elizabeth; Buckley, Brian; DiCicco-Bloom, Emanuel (Frontiers in Neuroscience, 2015)
The developing brain is sensitive to environmental toxicants such as methylmercury (MeHg), to which humans are exposed via contaminated seafood. Prenatal exposure in children is associated with learning, memory and IQ deficits, which can result from hippocampal dysfunction. To explore underlying mechanisms, we have used the postnatal day (P7) rat to model the third trimester of human gestation. We previously showed that a single low exposure (0.6 µg/gbw) that approaches human exposure reduced hippocampal neurogenesis in the dentate gyrus (DG) 24 hours later, including later proliferation and memory in adolescence. Yet, the vulnerable stem cell population and period of developmental vulnerability remain undefined. In this study, we find that P7 exposure of stem cells has long-term consequences for adolescent neurogenesis. It reduced the number of mitotic S-phase cells (BrdU), especially those in the highly proliferative Tbr2+ population, and immature neurons (Doublecortin) in adolescence, suggesting partial depletion of the later stem cell pool. To define developmental vulnerability to MeHg in prepubescent (P14) and adolescent (P21) rats, we examined acute 24 h effects of MeHg exposure on mitosis and apoptosis. We found that low exposure did not adversely impact neurogenesis at either age, but that a higher exposure (5 µg/gbw) at P14 reduced the total number of neural stem cells (Sox2+) by 23% and BrdU+ cells by 26% in the DG hilus, suggesting that vulnerability diminishes with age. To see if these effects may reflect changes in MeHg transfer across the blood brain barrier, we assessed Hg content in the hippocampus after peripheral injection and found that similar levels (~800 ng/gm) were obtained at 24 h at both P14 and P21, declining in parallel, suggesting that changes in vulnerability depend more on local tissue and cellular mechanisms. Together, we show that MeHg vulnerability depends on age, and that early exposure impairs later neurogenesis in older juveniles.